2017
DOI: 10.12688/f1000research.11063.2
|View full text |Cite
|
Sign up to set email alerts
|

Structural brain abnormalities in 12 persons with aniridia

Abstract: Background: Aniridia is a disorder predominately caused by heterozygous loss-of-function mutations of the PAX6 gene, which is a transcriptional regulator necessary for normal eye and brain development.  The ocular abnormalities of aniridia have been well characterized, but mounting evidence has implicated brain-related phenotypes as a prominent feature of this disorder as well.  Investigations using neuroimaging in aniridia patients have shown reductions in discrete brain structures and changes in global grey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Aniridia associated brain abnormalities affect six structures of the midline: the optic chiasm, the olfactory bulb, the pineal gland, both anterior and posterior commissures and the corpus callosum ( Abouzeid et al, 2009 ; Bamiou et al, 2007 ; Free et al, 2003 ; Grant et al, 2017 ; Sisodiya et al, 2001 ). They can all be hypoplastic, or even absent – except for the optic chiasm and the corpus callosum.…”
Section: Aniridia: Definition and Clinical Formsmentioning
confidence: 99%
“…Aniridia associated brain abnormalities affect six structures of the midline: the optic chiasm, the olfactory bulb, the pineal gland, both anterior and posterior commissures and the corpus callosum ( Abouzeid et al, 2009 ; Bamiou et al, 2007 ; Free et al, 2003 ; Grant et al, 2017 ; Sisodiya et al, 2001 ). They can all be hypoplastic, or even absent – except for the optic chiasm and the corpus callosum.…”
Section: Aniridia: Definition and Clinical Formsmentioning
confidence: 99%
“…Individuals may markedly underreport their daily difficulties compared to objective results on neuropsychological tests, or they may overreport their competency compared to the reports of family members. While prior studies on aniridia patients have described deficits observed on neuropsychological tests (Heyman et al, 1999 ; Yogarajah et al, 2016 ) and developmental delay (Grant et al, 2017 ; Grant et al, 2021 ; Netland et al, 2011 ), complete neuropsychological testing can be difficult for individuals with aniridia due to their vision loss. In this regard, neuropsychological tests may not fully evaluate cognitive dysfunction in aniridia.…”
Section: Discussionmentioning
confidence: 99%
“…Central nervous system abnormalities have been identified in the anterior and posterior commissure, pineal gland, corpus callosum, and anterior cingulate cortex of individuals with aniridia (Berntsson et al, 2020 ; Ellison-Wright et al, 2004 ; Grant et al, 2017 ; Hanish et al, 2016 ; Yogarajah et al, 2016 ). In addition, adults with PAX6 -associated aniridia exhibited an age-related decrease in cortical thickness in the inferior parietal lobe, prefrontal areas, and premotor areas in both hemispheres compared to the control group (Yogarajah et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Снижение интеллектуальных способностей у больных с врожденной аниридией (как правило, формирование умственной отсталости легкой степени) отмечено в еди-ничных исследованиях [33][34][35]. У пациентов с патогенными вариантами гена PAX6 также описано снижение функции вербальной рабочей памяти [26,31], что связывают с агенезией передней спайки головного мозга [26].…”
Section: когнитивные и психические нарушенияunclassified